Psychological impact of noise exposure among machine and non-machine operators in construction industry - Kee, Heng Yik; Nur Syafiqah, Fauzan; Widia, Mirta (IOP Publishing Ltd, 2019)
Noise hazard is reported as a serious issue among the construction industry in Malaysia. The aim of the study is to determine the personal noise exposure level and the prevalence of psychological health effect symptoms among the machine and non-machine operators on construction site in Malaysia. Sixty-one (61) construction workers were participated as respondents and categorized into machine and non-machine operators group. All respondents were monitored for 8 hours working time using personal noise dosimeter for personal noise monitoring. Questionnaires and interviewed sessions were used to determine the prevalence of psychological health effect symptoms. The results obtained reveal that the construction workers have high personal noise exposure level where machine operators are significantly higher compared to non-machine operators. The prevalence of psychological health effect symptoms among machine operators is 89% higher than the non-machine operators. Lastly, there is a significant positive relationship between the personal noise exposure level and the prevalence of psychological health effect symptoms among the construction workers.